Wear and surface roughness analysis of machining of Ti-6Al-4V under dry, wet and cryogenic conditions. (November 2019) - Ali Khan, Muhammad; Husain Imran Jaffery, Syed; Khan, Mushtaq; Ikramullah Butt, Shahid
Abstract: Use of cooling media contributes in elevation of desired responses owing to its cooling and lubrication effects especially in case of hard to cut materials like Ti-6Al-4V. This study aims to analyze the effect of cooling media in addition to cutting speed on responses including tool wear and surface integrity during turning. Results highlighted the effectiveness of cooling system in particular that of cryogenic media. Use of cryogenic media and cutting fluid enhanced tool life max by 33% and 21% respectively. At lower cutting speed surface roughness was improved by 13% and 8% by cryogenic media and cutting fluid respectively.